Quorum Sensing Coordinates Carbon and Nitrogen Metabolism to Optimize Public Goods Production in Pseudomonas fluorescens 2P24 - Jie Li; Mengxue Nie; Hongguang Ma; Xuanying Tao; Yanxia Sun; Xinyue Tu; Pingping Zhang; Li‐Qun Zhang; Rong Jia; Yong‐Xing He; Nannan Zhang; Honghua Ge (Advanced Science)
Abstract The coordination of public and private goods production is essential for bacterial adaptation to environmental changes. Quorum sensing (QS) regulates this balance by mediating the trade‐off between the communal benefits of “public goods,” such as siderophores and antibiotics, and the individual metabolic needs fulfilled by “private goods,” such as intracellular metabolites utilized for growth and survival. Pseudomonas fluorescens 2P24 harbors a LasI/LasR‐type QS system, MupI/MupR, which regulates mupirocin production through signaling molecules. This study explores how QS coordinates carbon and nitrogen metabolism to optimize the production of key secondary metabolites, including 2,4‐diacetylphloroglucinol (2,4‐DAPG), mupirocin, and siderophores, which serve as public goods. Loss of QS disrupts this balance by enhancing the Krebs cycle, denitrification, pyruvate anaplerosis, and ammonium assimilation, lead to halted 2,4‐DAPG and mupirocin synthesis and increased siderophore production. In the absence of QS, elevated siderophore production compensates for iron acquisition, ensuring rapid cellular growth. Under nutrient‐limited or high cell density conditions, MupR regulates carbon and nitrogen fluxes to sustain public goods production. These findings highlight QS as a key environmental sensor that fine‐tunes resource allocation, bacterial fitness, and adaptation to ecological and nutritional conditions, suggesting the potential for QS‐targeted approaches to enhance antibiotic production and agricultural sustainability.